Influence of the host diet on the performance of doryctobracon areolatus (Hymenoptera: Braconidae) - Ongaratto, S. [UNESP]; Pinto, K. J.; Mânica-Berto, R.; Nörnberg, S. D.; Gonçalves, R. S.; Garcia, M. S.; Nava, D. E. (FapUNIFESP (SciELO), 2020)
Fitness in parasitoids is generally influenced by host quality. We evaluated the development parameters of Doryctobracon areolatus (Hymenoptera: Braconidae) parasitoid on Anastrepha fraterculus (Diptera: Tephritidae) larvae, reared in artificial diets with different protein sources. Larvae of A. fraterculus were reared in the diets based on 1)raw wheat germ (control); 2) whole rice flour; 3) corn flour; and, 4) whole wheat flour + soybean meal. The larvae were used for the development of D. areolatus, to evaluate the number of offspring/female, emergence rate, sex ratio, egg-adult period, adult weight posterior tibia length and longevity. Larvae of A. fraterculus reared in the diets based on wheat germ and corn flour obtained a greater number of offspring, with shorter duration of egg-adult period for males and females. In diets with rice flour and corn flour, A. fraterculus larvae generated adults of D. areolatus with greater weight, longer tibia length and higher sex ratio, whereas larvae reared in wheat flour + soybean meal diet had a lower sex ratio. The diets based on rice flour and corn are the most appropriate for multiplication of the parasitoid.
Influência da dieta do hospedeiro na performance de doryctobracon areolatus (Hymenoptera: braconidae)
Keywords: Artificial diets; Biological control; Biological parameters; Mass rearing; Parasitoid